THE TREATMENT OF COLLOCATINS IN BILINGUAL DICTIONARIES PORTUGUESE - ENGLISH TO BRAZILIAN APPRENTICES - Damada, Gabrieli [UNESP] (Univ Fed Goias, Campus Catalao, 2017)
The theme of this study is the treatment of collocations in bilingual Portuguese-English dictionaries to Brazilian students. The main objective is to analyze and compare the way that occurs the record of collocations on microstructure of dictionaries analyzed. The corpus is composed of units formed from the semantic field fruits present in Oxford (2009) and Longman (2008) dictionaries. For the analysis we have used published works about bilingual lexicography and the structure of the dictionary, in particular, Carvalho (2001); Fuentes Moran (1997) and Nadin (2009). For this study we have tried to answer questions related to the use of the dictionary as a tool for expanding vocabulary, introducing how the lexical units, that we have chosen, appear in dictionaries analyzed and if these assist the user in the search for the word. The results showed that not always the dictionary structure collaborates in search of places and that the knowledge of the user's world is important.
Keywords: collocations; bilingual dictionaries; microstructure